Nestin Expression and the Survival of Patients With Digestive Tract Cancers: A Systematic Review and Meta-Analysis - Lumi Huang; Lihui Chen; Yiming Wang; Fucheng Zhang; Ting Wang; Dairong Li; Chunmei Wang; Huiwen Ma (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Several cancers have been associated with poor prognoses based on nestin, a confirmed marker of cancer stem cells. However, there is conflicting evidence regarding the prognostic value of tumor nestin expression in patients with digestive tract cancers. An investigation of the association between nestin and survival in patients with digestive tract cancers was performed in this meta-analysis. Materials and Methods: Meta-analyses were conducted using PubMed, Embase, and Web of Science databases to search for cohort studies. We analyzed the data using a random-effects model that incorporates differences between studies. Results: The pooled analysis showed a negative association between nestin expression and overall survival (hazard ratio: 1.38, 95% CI: 1.11 to 1.72, P = .004, I2 = 68%) and disease-free survival (hazard ratio: 1.48, 95% CI: 1.12 to 1.96, P = .005, I2 = 56%). Subgroup analysis showed that nestin expression was associated with poorer overall survival in gastric cancer (hazard ratio: 1.46, P < .001) and liver cancer (hazard ratio: 2.05, P < .001) patients, but not in colorectal cancer (hazard ratio: 1.03, P = .89) or pancreatic cancer (hazard ratio: 0.96, P = .80) patients. Further subgroup analysis showed a consistent association between nestin expression and poor overall survival in Asian and non-Asian studies, and in studies with univariate and multivariate regression models. Conclusion: To sum up, the presence of high nestin expression in digestive tract cancer patients is associated with poorer survival, particularly in patients with gastric and liver cancers Cite this article as: Huang L, Chen L, Wang Y, et al. Nestin expression and the survival of patients with digestive tract cancers: A systematic review and meta-analysis. Turk J Gastroenterol. 2023;34(9):902-910.